Jawabanmu

2016-09-15T07:32:12+07:00
A)
misalkan matik B = (1  3)
                               (2  4)

(B^-1)^-1 = B
B^-1 = 1/-2 (4  -3)
                   (-2  1)
   
        = (-2  3/2)
           (1   -1/2)

(B^-1)^-1 = -2 ( -1/2    -3/2)
                       ( -1        -2)
    
          = (1     3)
             (2     4)

terbukti bahwa (b^-1)^-1 = B

b)
B^t = (1  2)
         (3  4)
(B^t)^-1 = 1/-2 (4  -2)
                        (-3  1)
             = (-2       1)
                (3/2  -1/2) 

(B^-1)^t = (-2    1)
                (3/2  -1/2)

terbukti bahwa (B^t)^-1 = (B^-1)^t

1 5 1